2021
DOI: 10.1088/1361-6498/ac1a5d
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on low-dose radiation, the misconceptions, reality and moving forward

Abstract: Low dose radiation has been widely accepted by the radiation protection community as presenting a very low risk to human health, if any. Over-conservatism in optimisation principles and regulations have resulted in a disproportionate fear of radiation amongst the general public and government authorities alike, overlooking the great benefits nuclear science and techniques have brought to society as a whole. As such, the World Nuclear Association advocates for a recontextualisation of the radiation hazards with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Scientists are still exploring radiation's properties, and potential applications, as well as its hazards and risks of exposure (Cho et al, 2019). Several misconceptions about radiation have been researched recently, and this has helped to create greater public awareness about radiation's benefits and risks, leading to more informed decisionmaking regarding radiation-related issues (Lips et al, 2021;Neumann, 2014aNeumann, , 2014b.…”
Section: Research For Electromagnetic Radiationmentioning
confidence: 99%
“…Scientists are still exploring radiation's properties, and potential applications, as well as its hazards and risks of exposure (Cho et al, 2019). Several misconceptions about radiation have been researched recently, and this has helped to create greater public awareness about radiation's benefits and risks, leading to more informed decisionmaking regarding radiation-related issues (Lips et al, 2021;Neumann, 2014aNeumann, , 2014b.…”
Section: Research For Electromagnetic Radiationmentioning
confidence: 99%
“…Research activities can cover a wide range of practices; accordingly, the employees may be exposed to different levels of occupational exposure. Although radiation exposure in this type of activity have been reported to be mainly at low levels, previous and present investigations have demonstrated that the risks of low-dose radiation exposure, either at the occupational level or in chronic public exposure, are always of particular importance [1,2].…”
Section: Introductionmentioning
confidence: 60%